Analisis Perencanaan Pengelolaan Persediaan Urea dan Garam dengan Metode Forecasting pada PT. Energi Agro Nusantara - Dhea Lailiya Rahma; Yekti Condro Winursito (Pusat Riset dan Inovasi Nasional, 2024)
The efficiency of the production process is highly dependent on various factors, including the availability of raw materials. Therefore, every company is faced with the demand to enhance its managerial performance at all organizational levels, aiming to overcome various emerging challenges, especially those related to the production process. PT. Energi Agro Nusantara is confronted with the need to improve its raw material stock management to ensure compliance with market demands accurately and timely. The company is currently facing constraints, particularly in controlling product inventory, especially in terms of accurate calculations or predictions. This research is conducted to optimize the inventory of raw materials, specifically salt and urea, with the objective of meeting consumer needs. Forecasting methods are employed to determine the required daily production quantity. Furthermore, this research also aims to design a raw material control strategy to determine the necessary order quantities, ensuring that raw material inventory is maintained in accordance with production plans and forecasting results.